Phthalocyanine with a giant dielectric constant - Yazici, Aysegul; Unus, Nalan; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (Royal Soc Chemistry, 2012)
Compound 1 has been prepared by the reaction of 4-nitrophthalonitrile and trans-2-methoxy-4-(2-nitrovinil) phenol by the common method of nucleophilic substitution of an activated nitro group in an aromatic ring. The metallophthalocyanines 2, 3 were prepared by the reaction of a dinitrile derivative with Co(OAc)(2) or Zn(OAc)(2) in DMSO. The lutetium bis-(phthalocyaninato) complex 4 was obtained by treating the dinitrile derivative with lutetium acetate and DBU in 1-hexanol. The new compounds were characterized by elemental analyses, FT-IR, H-1-NMR, MALDI-TOF MS and UV/Vis spectral data. The spectroscopic data of the new compounds were in accordance with the structures. The temperature and frequency dependence of dielectric and conduction properties of the spin coated film of compounds (2-4) have been studied by fabricating metal-Pc-metal structures. The results show that compound 2 has giant dielectric constant. At a low range of frequency and room temperature, epsilon' is found to be equal to 2.33 x 10(6), 1.53 x 10(4) and 1.03 x 10(4) for 2, 3 and 4, respectively. The giant dielectric behavior of 2 is mainly attributed to Maxwell-Wagner polarization. The obtained results also indicated that the frequency dependence of the dielectric permittivity, epsilon'(omega), exhibits non-Debye type relaxation for all temperatures investigated. The ac conductivity results gave a temperature dependent frequency exponent s. The results were compared with the prediction of the Quantum Mechanical Tunneling and Correlated Barrier Hopping models.
Keywords: Gas-Sensing Properties; Rare-Earth Complexes; Double-Decker; Thin-Films; Metal; bis(Phthalocyaninato); Lutetium(Iii); Spectroscopy; Absorption; Oxidation